Bureau of Justice Statistics 2002: At glance - (:unkn) unknown (My University, 2016)
The Bureau of Justice Statisticscollects, analyzes, publishes, anddisseminates information on crime,criminal offenders, victims of crime,and the operation of justice systems atall levels of government. These dataare critical to Federal, State, and localpolicymakers in combating crime andensuring that administration of justiceis both efficient and evenhanded.